Communication Systems with Various Radio Access Schemes to Serve a UAV in Tropical Rain Areas - Hadiansyah, Walid Maulana; Hendrantoro, Gamantyo; Wirawan; Sirojuddin, Ahmad (International Conference on Communications, Signal Processing and their Applications (Online), 2024)
The millimeter-wave communication system has become one of the future broadband technologies, offering wide bandwidth and high data rates. However, in tropical rainy areas, the use of this communication system is susceptible to rain attenuation, significantly affecting performance quality. Additionally, obstacles and limited coverage areas can also degrade performance quality. Therefore, the communication system requires the assistance of Reconfigurable Intelligent Surface (RIS) to serve a user which do not have Line-of-Sight (LOS) signals from the base station (BS), or a user is far from BS. This paper discusses the performance of RIS compared to DF and AF relays, considering the movement of Unmanned Aerial Vehicle (UAV) as 3D mobile user and the impact of rain attenuation on millimeter-wave communication system performance. Furthermore, we explain the importance of determining relay coordinates to achieve better performance.